The Challenges and Recommendations for Gestational Diabetes Mellitus Care in India: A Review - Morampudi, Suman; Balasubramanian, Gayathri; Gowda, Arun; Zomorodi, Behsad; Patil, Anand Shanthanagowd (Frontiers in Endocrinology, 2017)
Gestational diabetes mellitus (GDM) is a primary concern in India affecting approximately five million women each year. Existing literature indicate that pre-diabetes and diabetes affect approximately six million births in India alone, of which 90% are due to GDM. Studies reveal that there is no consensus among physicians and healthcare providers in India regarding management of GDM pre-partum and post-partum; despite available guidelines. Also, there is no consensus among physicians as to when a woman should undergo Oral Glucose Tolerance Test after delivery. This clearly shows that management of GDM is challenging and controversial in India due to conflicting guidelines and treatment protocols, despite availability of straightforward protocols for screening and management. Also, a collaborative approach remains a key for GDM management, as patient compliance and proper educational interventions promote better pregnancy outcomes. Management of GDM plays a pivotal role, as women with GDM have an increased chance of developing diabetes mellitus 5–10 years after pregnancy. Also, children born in GDM pregnancies face an increased risk for obesity and type 2 diabetes. The cornerstone for the management of GDM is glycemic control and quality nutritional intake. GDM management is complex in India and existing challenges are multifactorial. However, there is little published data outlining these challenges. This review gives an account of some of the key challenges from self-management and healthcare provider perspective. The recommendations in this review provide insights for building a more structured model for GDM care in India. This research has several practical applications. Firstly, it points to reaching a consensus on approaches for screening, diagnosis and treatment of care across clinical practices in the nation that can aid in overcoming certain challenges observed. Secondly, it highlights the importance to build capacities and capabilities, especially in resource-limited settings. Health education among pregnant women remains a priority to resolve issues related to self-management. More broadly, further research, specifically qualitative to determine forthcoming challenges with respect to patients, caregivers, providers and policy makers, and provide solutions fitted to practice setting and demographic background is essential.